The Effect of Discovery Learning on Elementary School Students’ Critical Thinking Skills and Learning Outcomes - Puliya Kusumawati; Suriswo Suriswo (Journal of Educational Sciences, 2026)
This study is motivated by the low level of critical thinking skills and learning outcomes among elementary school students, which is closely related to the continued dominance of teacher-centered instructional practices. Therefore, this study aims to examine the effect of the Discovery Learning model on elementary school students’ critical thinking skills and learning outcomes. A quantitative method with a quasi-experimental design was employed, involving an experimental group and a control group. The participants consisted of 93 fifth-grade students at SD Negeri Beji, Pemalang Regency, in the 2025/2026 academic year. Data were collected using multiple-choice achievement tests to measure learning outcomes and questionnaires to assess students’ critical thinking skills. Prior to hypothesis testing, the data were confirmed to meet classical assumption requirements. Data analysis was conducted using simple linear regression with the assistance of SPSS software. The results revealed that the Discovery Learning model had a significant positive effect on students’ critical thinking skills and learning outcomes. These findings indicate that Discovery Learning is an effective instructional model for promoting active learning, strengthening higher-order thinking skills, and improving academic achievement in elementary education.